Riding the Windhorse: Manic-Depressive Disorder and the Quest for Wholeness - Corrington, Robert S. (Hamilton Books, 2003)
In this moving account of his struggles with manic-depressive disorder, distinguished philosopher Robert S. Corrington, creator of the school of ecstatic naturalism, presents a compelling argument for rethinking the nature of this malady. Having inherited the disorder from his mother, a gifted actress who struggled with her own form of it until her death, he developed crucial survival strategies that he recommends to other sufferers. In Riding the Windhorse, Corrington details the latest medical, psychological, and spiritual thinking about bipolar disease; a disorder characterized by extreme mood swings and responsible for many untimely deaths each year. Surprisingly, however, manic-depression is also found in almost all forms of genius and Corrington presents two detailed case studies showing this correlation. Riding the Windhorse represents one person's eventual triumph over a potentially crippling disease by demonstrating how creativity and the quest for wholeness can support the erratic flight of the windhorse of manic-depression.